Acid catalyzed nitrile thiolysis of 3-amino-acrylonitriles, toward the synthesis of 3, 4-substituted-5-amino-isothiazoles. Issue 20 (13th May 2015) - Kuklish, Steven L.; Backer, Ryan T.; Fisher, Matthew J.; Kempema, Aaron M.; Mauldin, Scott C.; Merschaert, Alain
Graphical abstract: Abstract: Application of an acid-catalyzed thioamidation of β-amino-acrylonitriles to the corresponding β-amino-thioacrylamides toward the synthesis of 3, 4-substituted-5-amino-isothiazoles is described. The greatest yields were observed for examples with electron rich aromatic systems. This method uses inexpensive and easily handled reagents.